Perfil imunohistoquímico da proteína P16INK4a associado a fatores histológicos e ao HPV no câncer de pênis - MARTINS, Vicenilma de Andrade (2017)
Infection by HPV is described in the literature in 30-50% of cases of penile cancer. The immunohistochemical of p16INK4a is used as an indication of the presence of HPV and prognostic marker for squamous carcinomas various sites. However, its role in penile carcinoma has not yet been completely elucidated. The aim of the study was to prospectively analyze whether the expression of p16INK4a is associated with the presence of HPV and histological parameters in penile cancer. A prospective study was conducted in the period 2014 to 2016 with 55 cases of patients with penile carcinoma. HPV DNA was detected by PCR in fresh tumor tissue and immunohistochemistry for analysis of p16INK4a protein in paraffin waxed tissue. The evaluation of histological parameters was performed after total inclusion of the tumor tissue. HPV DNA (lowrisk and high-risk genotypes) was found in 49 (89.1%) cases, 46 (83.6%) HR-HPV. Of the 22 p16INK4a positive cases, HR-HPV DNA was present in 21 (95.5%) of them (p = 0.032). Regarding histological parameters, p16INK4a and HR-HPV were significantly associated only with the tumor subtype (p = 0.036 and p = 0.032, respectively), being that, all carcinomas with basaloid characteristics were positive p16INK4a. Using a fresh tissue sample, our sample showed the highest incidence of HPV in the literature. Expression of the p16INK4a protein was significantly associated with the presence of high oncogenic HPV virus and may serve as a marker for the presence of this virus. The p16INK4a protein was not associated with the histological prognostic parameters, except for the tumor subtype.